Flexible DLC coating method

By forming a composite structure of nanocrystalline diamond film and silicon nitride film on the substrate, and then coating elastomeric material and opening design, the flexibility and flexibility of the DLC coating are solved, and a high hardness and low friction DLC composite film is achieved, which is suitable for automobiles, aerospace and other fields.

CN120231049APending Publication Date: 2025-07-01SAE TECH DELEVOPMENT DONGGUAN
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311847036.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-28
Publication Date
2025-07-01

AI Technical Summary

Technical Problem

The existing DLC ​​coatings are unable to meet the special needs of flexibility and bendability, limiting their application in emerging fields.

Method used

A first nanocrystalline diamond film is formed on the substrate, and then a silicon nitride film and a second nanocrystalline diamond film are deposited thereon to form a DLC composite film, and an elastomeric material is coated thereon to form a plurality of openings to improve flexibility.

Benefits of technology

It realizes the high hardness, high thermal stability and low friction coefficient of DLC composite film, and has flexibility and flexibility, which is suitable for multiple fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120231049A_ABST
    Figure CN120231049A_ABST
Patent Text Reader

Abstract

The invention discloses a flexible DLC (diamond-like carbon) coating method, which comprises the following steps: forming a first nanocrystalline drill film on a base material, forming a silicon nitride film on the first nanocrystalline drill film, forming a second nanocrystalline drill film on the silicon nitride film, forming a DLC composite film by the first nanocrystalline drill film, the silicon nitride film and the second nanocrystalline drill film, and forming a flexible DLC film on the DLC composite film. The elastomer material is formed on the DLC composite film, so that the DLC composite film can realize operations such as bending, and in addition, the DLC composite film has excellent performances such as high hardness, high thermal stability and low friction coefficient, and has wide application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of coating technologies, and particularly to a method for flexible DLC coating. Background Art

[0002] DLC is a material with excellent properties such as high hardness, high thermal stability, and low friction coefficient, and is widely used in fields such as automobiles, aerospace, and machining. However, traditional DLC coatings have relatively strict limiting conditions, such as the roughness of steel and temperature, and cannot meet some special requirements, such as flexibility and bendability. Therefore, there is an urgent need for a technology that can manufacture flexible DLC to meet the needs of emerging fields. Summary of the Invention

[0003] Embodiments of the present invention aim at the deficiencies in the prior art and provide a method for flexible DLC coating, including:

[0004] Forming a first nanocrystalline diamond film on a substrate;

[0005] Forming a silicon nitride thin film on the first nanocrystalline diamond film;

[0006] Forming a second nanocrystalline diamond film on the silicon nitride thin film; wherein, the first nanocrystalline diamond film, the silicon nitride thin film, and the second nanocrystalline diamond film constitute a DLC composite film;

[0007] Forming an elastomeric material on the DLC composite film.

[0008] As a preferred solution, the forming of the first nanocrystalline diamond film on the substrate specifically includes:

[0009] Placing the substrate in a chemical vapor deposition reaction chamber, and depositing the first nanocrystalline diamond film on the surface of the substrate by chemical vapor deposition. The deposition conditions are: the temperature of the reaction chamber is 700 - 900 °C, the reaction gases are methane and hydrogen, the pressure is 5 - 6 torr, and the reaction time is 40 - 60 minutes.

[0010] As a preferred solution, the ratio of methane to hydrogen when forming the first nanocrystalline diamond film is 1:5.

[0011] As a preferred solution, the forming of the silicon nitride thin film on the first nanocrystalline diamond film specifically includes:

[0012] Using radio frequency magnetron sputtering, generating plasma through nitrogen and argon, using a silicon target as the target, and depositing the silicon nitride thin film on the first nanocrystalline diamond film. The deposition conditions are: the deposition rate is 0.1 - 0.3 nm / s, the DC voltage is 200 V, the radio frequency power is 200 W, and the deposition time is 25 - 30 minutes.

[0013] As a preferred solution, forming a second nanocrystalline diamond film on the silicon nitride film specifically includes:

[0014] Placing the substrate with the silicon nitride film formed thereon in a chemical vapor deposition reaction chamber, and depositing a second nanocrystalline diamond film on the surface of the substrate by chemical vapor deposition. The deposition conditions are: the temperature of the reaction chamber is 700 - 900 °C, the reaction gases are methane and hydrogen, the air pressure is 5 - 6 torr, and the reaction time is 40 - 60 minutes.

[0015] As a preferred solution, forming an elastomeric material on the DLC composite film specifically includes:

[0016] Coating the elastomeric material on the DLC composite film by brushing or rolling.

[0017] As a preferred solution, the elastomeric material is polyurethane or silica gel.

[0018] After forming the elastomeric material on the DLC composite film, it further includes:

[0019] Forming a plurality of openings on the elastomeric material, wherein the distance between the bottom surface of the opening and the second nanocrystalline diamond film is greater than zero.

[0020] As a preferred solution, the total cross-sectional area of the plurality of openings is less than 1 / 30 of the cross-sectional area of the elastomeric material.

[0021] As a preferred solution, at least part of the inner bottom surface of the opening is recessed inward.

[0022] Compared with the prior art, the beneficial effects of the embodiments of the present invention are as follows: The embodiments of the present invention provide a flexible DLC coating method. First, a first nanocrystalline diamond film is formed on a substrate, then a silicon nitride film is formed on the first nanocrystalline diamond film, and then a second nanocrystalline diamond film is formed on the silicon nitride film. Among them, the first nanocrystalline diamond film, the silicon nitride film, and the second nanocrystalline diamond film constitute a DLC composite film, and an elastomeric material is formed on the DLC composite film, so that the DLC composite film can achieve operations such as bending. In addition, the DLC composite film has excellent properties such as high hardness, high thermal stability, and low friction coefficient, and has wide application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a schematic flow chart of the flexible DLC coating method in the embodiments of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.

[0025] Please refer to Figure 1 , which is a schematic flow chart of the flexible DLC coating method in the embodiments of the present invention.

[0026] The flexible DLC coating method of the embodiments of the present invention includes:

[0027] Step S101, forming a first nanocrystalline diamond film on a substrate;

[0028] Step S102, forming a silicon nitride film on the first nanocrystalline diamond film;

[0029] Step S103, forming a second nanocrystalline diamond film on the silicon nitride film; wherein, the first nanocrystalline diamond film, the silicon nitride film and the second nanocrystalline diamond film constitute a DLC composite film;

[0030] Step S104, forming an elastomeric material on the DLC composite film.

[0031] In this embodiment, a first nanocrystalline diamond film is first formed on a substrate, then a silicon nitride film is formed on the first nanocrystalline diamond film, and then a second nanocrystalline diamond film is formed on the silicon nitride film. Among them, the first nanocrystalline diamond film, the silicon nitride film and the second nanocrystalline diamond film constitute a DLC composite film, and an elastomeric material is formed on the DLC composite film, so that the DLC composite film can perform operations such as bending. In addition, the DLC composite film has excellent properties such as high hardness, high thermal stability and low friction coefficient, and has wide application value.

[0032] In specific implementation, the substrate refers to a workpiece. In order to improve the performance of the workpiece according to actual needs, coating is usually performed on the surface of the workpiece. The flexible DLC coating method of the embodiments of the present invention provides a surface coating for the workpiece. Among them, the workpiece can be, for example, a workpiece in the fields of automobiles, aerospace, machining, etc., such as steel.

[0033] In specific implementation, the silicon nitride film has good thermal stability. In addition, setting the silicon nitride film between the first nanocrystalline diamond film and the second nanocrystalline diamond film can avoid the direct overlap of the two nanocrystalline diamond films, which may affect the strength due to excessive thickness, and further ensure that the DLC composite film can perform operations such as bending.

[0034] In some embodiments, the step S101 "forming a first nanocrystalline diamond film on a substrate" specifically includes:

[0035] Place the substrate in a chemical vapor deposition reaction chamber, and deposit a first nanocrystalline diamond film on the surface of the substrate by chemical vapor deposition (CVD). The deposition conditions are as follows: the temperature of the reaction chamber is 700 - 900 °C, the reaction gases are methane and hydrogen, the pressure is 5 - 6 torr, and the reaction time is 40 - 60 minutes.

[0036] Exemplarily, the ratio of methane to hydrogen when forming the first nanocrystalline diamond film is 1:5. The thickness of the first nanocrystalline diamond film is 10 - 15 nanometers.

[0037] In some embodiments, the step S102 "forming a silicon nitride thin film on the first nanocrystalline diamond film" specifically includes:

[0038] Use radio frequency magnetron sputtering to generate plasma through nitrogen and argon, and use a silicon target as the target to deposit a silicon nitride thin film on the first nanocrystalline diamond film. The deposition conditions are as follows: the deposition rate is 0.1 - 0.3 nm / s, the DC voltage is 200 V, the radio frequency power is 200 W, and the deposition time is 25 - 30 minutes. The thickness of the silicon nitride thin film is 50 - 60 nanometers.

[0039] In some embodiments, the step S103 "forming a second nanocrystalline diamond film on the silicon nitride thin film" specifically includes:

[0040] Place the substrate with the silicon nitride thin film formed thereon in a chemical vapor deposition reaction chamber, and deposit a second nanocrystalline diamond film on the surface of the substrate by chemical vapor deposition. The deposition conditions are as follows: the temperature of the reaction chamber is 700 - 900 °C, the reaction gases are methane and hydrogen, the pressure is 5 - 6 torr, and the reaction time is 40 - 60 minutes. The thickness of the first diamond-like carbon film layer is 10 - 15 nanometers. The thickness of the second nanocrystalline diamond film is 10 - 15 nanometers.

[0041] Exemplarily, the deposition conditions of the second nanocrystalline diamond film in this embodiment are the same as those of the first nanocrystalline diamond film.

[0042] In some embodiments, the step S101 "forming an elastomeric material on the DLC composite film" specifically includes:

[0043] The elastomeric material is coated on the DLC composite film by brushing or rolling. Specifically, the elastomeric material is polyurethane or silica gel. Of course, the elastomeric material can also be selected according to actual usage requirements and will not be elaborated further here. By coating the elastomeric material on the DLC composite film, the DLC composite film can be bent and other operations can be achieved. The thickness of the elastomeric layer is 150 - 200 nanometers.

[0044] In specific implementation, for the workpiece with the DLC composite film prepared by using the flexible DLC coating method provided in the embodiment of the present invention, the thermal stability test and bending test are carried out on the workpiece with the DLC composite film. The results show that at 800 °C, the surface hardness and friction coefficient of the DLC composite film change less; and in the bending test, the surface of the DLC composite film can still remain intact after being bent by 180°.

[0045] In some embodiments, after forming the elastomeric material on the DLC composite film, it further includes:

[0046] Forming a plurality of openings on the elastomeric material, wherein the distance between the bottom surface of the opening and the second nanocrystalline diamond film is greater than zero.

[0047] In this embodiment, by forming a plurality of openings on the elastomeric material, it is easier to achieve bending, thereby further improving the bendability of the DLC composite film. At the same time, since the distance between the bottom surface of the opening and the second nanocrystalline diamond film is greater than zero, that is, the elastomeric material and the second nanocrystalline diamond film are always in close contact, which ensures that the elastomeric material can improve the bendability of the DLC composite film.

[0048] Specifically, the total cross-sectional area of the plurality of openings is less than 1 / 30 of the cross-sectional area of the elastomeric material.

[0049] In this embodiment, since the total cross-sectional area of the plurality of openings is less than 1 / 30 of the cross-sectional area of the elastomeric material, it can be ensured that bending can be achieved more easily, and at the same time, the elastomeric material has good strength to ensure that the DLC composite film can achieve reliable bending.

[0050] Specifically, at least part of the inner bottom surface of the opening is recessed inward.

[0051] In this embodiment, the inner bottom surface of the opening is recessed inward, which means that the side of the opening close to the second nanocrystalline diamond film is recessed toward the second nanocrystalline diamond film. Therefore, the edge height of the inner bottom surface of the opening is greater than that of the middle part of the inner bottom surface. In this way, when the bending direction of the DLC composite film is the same as the recessed direction of the inner bottom surface of the opening, the edge area of the inner bottom surface of the opening has a strengthening effect, which can ensure the strength of the elastomeric material, thus ensuring reliable bending for the DLC composite film. At the same time, the middle part of the inner bottom surface of the opening is convenient for achieving a larger bending angle.

[0052] Specifically, at least part of the inner bottom surface of the opening bulges outward.

[0053] In this embodiment, the inner bottom surface of the opening bulges outward, which means that the side of the opening close to the second nanocrystalline diamond film bulges in the direction away from the second nanocrystalline diamond film. Therefore, the edge height of the inner bottom surface of the opening is smaller than that of the middle part of the inner bottom surface. In this way, when the bending direction of the DLC composite film is the same as the bulging direction of the inner bottom surface of the opening, the middle part of the opening has a strengthening effect, which can ensure the strength of the elastomeric material, thus ensuring reliable bending for the DLC composite film. At the same time, the edge of the inner bottom surface of the opening is convenient for achieving a larger bending angle.

[0054] It should be noted that, for some of the openings, the inner bottom surface can be recessed inward, and for some of the openings, the inner bottom surface can bulge outward; or the inner bottom surfaces of all the openings can be recessed inward; or the inner bottom surfaces of all the openings can bulge outward.

[0055] Specifically, the elastomeric material is also provided with a plurality of grooves. The plurality of grooves and the plurality of openings are in a one-to-one correspondence. The grooves communicate with the openings. The cross-sectional area of the grooves is larger than the cross-sectional area of the openings to achieve a larger bending angle; the distance between the bottom surface of the grooves and the second nanocrystalline diamond film is greater than 9 / 10 of the thickness of the elastomeric material to ensure that the grooves with a small depth can improve the bendability while ensuring that the elastomeric material can perform the bending operation for the DLC composite film.

[0056] Compared with the prior art, the beneficial effects of the embodiments of the present invention are as follows: The embodiments of the present invention provide a flexible DLC coating method. First, a first nanocrystalline diamond film is formed on a substrate, then a silicon nitride thin film is formed on the first nanocrystalline diamond film, and then a second nanocrystalline diamond film is formed on the silicon nitride thin film. Among them, the first nanocrystalline diamond film, the silicon nitride thin film, and the second nanocrystalline diamond film constitute a DLC composite film. An elastomeric material is formed on the DLC composite film, so that the DLC composite film can perform operations such as bending. In addition, the DLC composite film has excellent properties such as high hardness, high thermal stability, and low friction coefficient, and has wide application value.

[0057] The above are only the preferred embodiments of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the technical principle of the present invention, several improvements and substitutions can be made, and these improvements and substitutions should also be regarded as the protection scope of the present invention.

Claims

1. A flexible DLC coating method, characterized in that, Comprising: Forming a first nanocrystalline diamond film on a substrate; Forming a silicon nitride thin film on the first nanocrystalline diamond film; Forming a second nanocrystalline diamond film on the silicon nitride thin film; wherein, the first nanocrystalline diamond film, the silicon nitride thin film and the second nanocrystalline diamond film constitute a DLC composite film; Forming an elastomeric material on the DLC composite film.

2. The flexible DLC coating method according to claim 1, characterized in that, The forming of the first nanocrystalline diamond film on the substrate specifically includes: Placing the substrate in a chemical vapor deposition reaction chamber, and depositing the first nanocrystalline diamond film on the surface of the substrate by chemical vapor deposition. The deposition conditions are: the temperature of the reaction chamber is 700 - 900 °C, the reaction gases are methane and hydrogen, the pressure is 5 - 6 torr, and the reaction time is 40 - 60 minutes.

3. The flexible DLC coating method according to claim 2, wherein The ratio of methane to hydrogen when forming the first nanocrystalline diamond film is 1:

5.

4. The flexible DLC coating method according to claim 1, characterized in that The forming of the silicon nitride thin film on the first nanocrystalline diamond film specifically includes: Using radio frequency magnetron sputtering method, generating plasma through nitrogen and argon, using a silicon target as the target, and depositing the silicon nitride thin film on the first nanocrystalline diamond film. The deposition conditions are: the deposition rate is 0.1 - 0.3 nm / s, the DC voltage is 200 V, the radio frequency power is 200 W, and the deposition time is 25 - 30 minutes.

5. The flexible DLC coating method according to claim 1, characterized in that, The forming of the second nanocrystalline diamond film on the silicon nitride thin film specifically includes: Placing the substrate with the formed silicon nitride thin film in a chemical vapor deposition reaction chamber, and depositing the second nanocrystalline diamond film on the surface of the substrate by chemical vapor deposition. The deposition conditions are: the temperature of the reaction chamber is 700 - 900 °C, the reaction gases are methane and hydrogen, the pressure is 5 - 6 torr, and the reaction time is 40 - 60 minutes.

6. The flexible DLC coating method according to claim 1, wherein, The forming of the elastomeric material on the DLC composite film specifically includes: Coating the elastomeric material on the DLC composite film by brush coating method or roller coating method.

7. The flexible DLC coating method according to claim 1, characterized in that, The elastomeric material is polyurethane or silicone.

8. The flexible DLC coating method according to any one of claims 1-7, characterized in that, After forming the elastomeric material on the DLC composite film, it further includes: Forming a plurality of openings on the elastomeric material, wherein the distance between the bottom surface of the opening and the second nanocrystalline diamond film is greater than zero.

9. The flexible DLC coating method according to claim 8, wherein, The total cross-sectional area of the plurality of openings is less than 1 / 30 of the cross-sectional area of the elastomeric material.

10. The flexible DLC coating method according to claim 8, wherein, At least part of the inner bottom surface of the opening is recessed inward.